2011
DOI: 10.1007/s10165-010-0406-3
|View full text |Cite
|
Sign up to set email alerts
|

Postmarketing surveillance of safety and effectiveness of etanercept in Japanese patients with rheumatoid arthritis

Abstract: Our aim was to evaluate real-world safety and effectiveness in a 6-month postmarketing surveillance study covering all Japanese patients with rheumatoid arthritis (RA) who received etanercept during a 2-year period. Data for 13,894 patients (1334 sites) enrolled between March 2005 and April 2007 were collected. Adverse events (AEs) and serious adverse events (SAEs) were reported in 4336 (31.2%) and 857 (6.2%) patients, respectively. The most frequent AEs were injection site reactions (n = 610, 4.4%) and rash (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
38
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 21 publications
(4 reference statements)
10
38
1
1
Order By: Relevance
“…Post-marketing surveillance studies in Japan indicated that the frequencies of drug-related ILD in Japanese RA patients treated with infliximab or etanercept were 0.5% and 0.6%, respectively [24,77]. In accordance with findings in TNF antagonist-naïve RA patients, men were twice as frequently affected by ILD as women [77].…”
Section: Interstitial Lung Diseasesupporting
confidence: 76%
See 1 more Smart Citation
“…Post-marketing surveillance studies in Japan indicated that the frequencies of drug-related ILD in Japanese RA patients treated with infliximab or etanercept were 0.5% and 0.6%, respectively [24,77]. In accordance with findings in TNF antagonist-naïve RA patients, men were twice as frequently affected by ILD as women [77].…”
Section: Interstitial Lung Diseasesupporting
confidence: 76%
“…According to a systematic review by the Spanish Study Group of Autoimmune Diseases (the BIOGEAS project), 14 of 1842 (0.76%) patients enrolled in clinical trials of TNF antagonists developed drug-induced lupus (DIL) [74]. Post-marketing surveillance yielded lower incidence rates [74,77]. In the pivotal trials examining the efficacy and safety of abatacept in the treatment of RA, SLE and a lupus-like syndrome occurred at markedly lower rates than during TNF blockade (0.05/100 PY and 0.01/100 PY, respectively) [25].…”
Section: Lupus and Lupus-like Diseasementioning
confidence: 99%
“…The mortality of patients with non-HIV PCP is diverse and ranges from 0 to 70% [1,4,5,6,7,8,9], compared with the mortality of HIV-infected PCP patients which ranges from 10 to 20% [1,10]. The higher mortality among non-HIV patients has been attributed to severe lung inflammation [1,5], although the exact etiologies responsible for the differences in mortality have not yet been determined.…”
Section: Discussionmentioning
confidence: 99%
“…There is no culture method for determining the presence of P. jirovecii [4], so microscopic findings such as Grocott or Diff-Quik staining are commonly used. Although Diff-Quik is specific and useful, it requires high expertise and has a low sensitivity in the diagnosis of non-HIV PCP [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation